Reversible cerebellar involvement in the idiopathic hypereosinophilic syndrome - Diaz, F. (BMJ Group, 1999)
We report a patient with cerebellar manifestations due to the idiopathic hypereosinophilic syndrome, in whom magnetic resonance imaging (MRI) showed hyperintense lesions in both cerebellar hemispheres. Following steroids and hydroxyurea administration, the lesions on MRI disappeared, suggesting that the pathogenetic mechanism was reversible and did not cause significant structural damage. To our knowledge, the resolution of the abnormal MRI findings have not been reported to date in the idiopathic hypereosinophilic syndrome.   Keywords: hypereosinophilic syndrome; cerebellum; magnetic resonance imaging; hydroxyurea